Sistem Informasi Penjualan Pada Toko Al-Idan Variasi Motor Kelurahan Karang Baru, Kecamatan Mataram - Yulia Arianti; Maulana Ashari (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
Current trends online shopping via the Internet has mushroomed in Indonesia, even very well known by the general public. The many diverse ease of shopping and various kinds of goods and services offered, making the online shop to make Indonesian society as one of the "shopping" a new addition to the shopping center. The proliferation of online shop the many business opportunities targeting teens as consumers., The advantages of online business shop apart easily in the promotion, are also highly efficient because it only requires a subscription fee for running the business. Production or sales system settings influence the level of acceptance of the company's revenue. Therefore, companies have to actually supervise and control the activities of sales and inventory by implementing an adequate system, so that the sales target can be achieved ,. Moreover how the transaction by writing to the bill of sale that takes a long time, which resulted in the customer service to be slower. Therefore store Al-Idan variation Mataram motors require a sales and information systems Stock items that can help process data documentation and solve the problems of data loss. With the computerized system, makes the process of selling and stock goods becomes faster. During this process of recording sales data and inventory simply by collecting a memorandum - a memorandum at a time and record it in a book report. With the web site at Al-Idan be easier for consumers to buy motorcycle accessories and spare parts that do not need to come to the store.